DISHARMONISASI ANTARA MAHKAMAH KONSTITUSI DAN MAHKAMAH AGUNG DIHUBUNGKAN DENGAN ASAS KEPASTIAN HUKUM (Studi Putusan Nomor 30/PUU-XVI/2018 dan Putusan Nomor 65 P/HUM/2018 dengan Pemohon Oesman Sapta Odang) - Angghie Permatasari; Lusy Liany; Amir Mahmud (JURIS (Jurnal Ilmiah Syariah), 2020)
Disharmonization between the Constitutional Court's Decision and the Supreme Court's Decision related to the case of the executive (functionary) of political parties in the nomination of DPD RI members in the 2019 General Election. The research method used was normative juridical research, using secondary data. The results of the discussion are: First, disharmony between the Constitutional Court Decision Number 30 / PUU-XVI / 2018 and the Supreme Court Decision Number 65 P / HUM 2018 in the nomination of DPD RI members in the 2019 General Election related to the phrase "other work" in Article 182 letter l of the Election Law. Second, as a result of the two decisions, the Election Commission issued a KPU Regulation as the implementation of the Constitutional Court's Decree containing a ban on the "functionary" management of political parties not allowed to nominate as members of the DPD RI in 2019. Third, in the arguments that contradict each other / disharmony Islamic teachings are familiar with Islamic teachings. the existence of Ta'arud Al-Adillah by way of Al-Jam'u wa taufiq. As for the suggestions in this paper: First, it is hoped that in the future all testing of legislation will be made as one roof in the Constitutional Court or in the Constitutional Question. Second, the KPU is still guided by the latest PKPU in the implementation of the coming elections as the implementation of the Constitutional Court's decision.